Conflict Avoidance Behavior in Supplier Negotiation: A Case Study of Bopan Cake Samarinda - Alizha Putri Endriani; Aureline Agny Masiku; Kennya Nur Syahada; Paskah Aprindah Sitompul; Verny Marceli Sisilia Saputri; Muhammad Ramadhani Kesuma (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2026)
Small and medium enterprises (MSMEs) in the food service sector frequently prioritize relational harmony over economic rationality when managing supplier relationships, yet the operational and financial consequences of this orientation remain underexplored in the Indonesian context. This study analyzes conflict avoidance behavior and its implications for cost efficiency, product quality, and supplier relationship management at Bopan Cake Samarinda, a micro-scale bakery enterprise. Using a qualitative case study design, data were collected through semi-structured interviews with the business owner and direct non-participatory observation of daily operational activities. Thematic analysis identified five interlocking behavioral and operational patterns: (1) an avoidance-style conflict management that suppresses quality complaints to preserve supplier harmony; (2) harmony-seeking behavior that generates negative feedback barriers in the supply chain; (3) an independent, quality-driven procurement strategy; (4) perishable goods risk exposure due to organizational silence; and (5) constrained bargaining power offset by wholesale volume tactics. Findings indicate that conflict avoidance simultaneously protects product quality standards and erodes cost efficiency through uncompensated raw material waste. The study contributes an empirical case from East Kalimantan to the broader literature on organizational behavior in MSMEs and proposes an assertive communication model as a cost-neutral improvement pathway for similar small enterprises.